Pendidikan Anti Bullying Persfektif Abdullah Nasih Ulwan - Sa'adah Erliani (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Abstract: Many cases of violence that occur in schools. This needs special attention so that violence in educational institutions does not recur. Anti-bullying children's education perspective Abdullah Nasih Ulwan is a way for Islamic education experts to explain the concept of education without violence. This research is a library research, which is a literature study through library research by discussing anti-bullying education in the book "Tarbiyatul Aulad Fil Islam" by Abdullah Nashih Ulwan. data collection techniques through documentation in the form of the book Tarbiyatul Aulad Islam fil by Abdullah Nashih Ulwan. Research results: 1. Bullying is a form of violence that occurs in the world of education. Bullying occurs because of the influence of the family environment, the community and also the influence of the school environment. 2 ways to overcome them according to Abdullah still Ulwan in his book Tarbiyatul Aulad Islamic Films is by applying Faith education, moral education, physical education, resource education, psychiatric education, social education and sex education. Keywords: education, anti-bullying, Nashih Ulwan